Zirconium-89-labelled rituximab PET-CT in orbital inflammatory disease - Laban, Kamil G. (EJNMMI Res, 2019)
BACKGROUND: Orbital inflammatory diseases are a heterogenic group of conditions that often entail a difficult diagnostic process and many patients are treatment resistant. Inflammatory diseases can be visualized by Zirconium-89-labelled rituximab PET-CT ((89)Zr-rituximab PET/CT). In this study, we describe our experience and possible potential of the (89)Zr-rituximab PET/CT for diagnostic and therapeutic management of refractory orbital inflammation. RESULTS: Retrospectively, (89)Zr-rituximab uptake was assessed and related to clinical data. The main outcome measures were the characteristics of the scan and the clinical relation of uptake with the diagnostic process and treatment effectivity. Twelve patients with thyroid eye disease (TED) and suspected idiopathic orbital inflammation (IOI) were scanned. Six patients had a strong (89)Zr-rituximab uptake and showed a focal distribution within the lesion. Four patients (one TED, three IOI) responded well to rituximab treatment after a positive scan. (89)Zr-rituximab PET/CT was essential to the diagnosis of optic nerve meningioma in one patient. CONCLUSION: (89)Zr-rituximab PET/CT has the potential to be a powerful tool for the detection of B cell-mediated disease within the orbit and ocular adnexa. This technique can be a valuable addition for diagnosing diseases around the eye and can potentially predict rituximab treatment response in patients with refractory inflammation.